Influence of metakaolin and Recron 3s fiber on mechanical properties of fly ash replaced concrete. (10th December 2020) - Nanda, Radhikesh P.; Mohapatra, Arup Kumar; Behera, Biplab
Highlights: Concrete incorporating fly ash, metakaolin and Recron 3s fiber has been studied. The compressive strength, split tensile and flexural strength have been investigated. Cement replacement with 10% Fly ash, 5% Metakaolin & 0.2% Recron 3s fiber enhanced the mechanical properties. Abstract: In this study, an experimental study was carried to investigate the effects of fly ash (FA) and metakaolin (MK) as a partial replacement for Portland slag cement (PSC), and Recron 3s fiber as an additive, on the mechanical properties of concrete. Compressive strength, split tensile strength and flexural strength were investigated for separate mixtures prepared from the different % replacement of metakaolin (5%, 10%, and 15%) and fly ash (10%, 20%, and 30%) by weight of cement with constant 0.2% of Recron 3s fiber. Results showed that blending of metakaolin, fly ash and Recron 3s fiber enhance overall mechanical properties of concrete. However, with only MK replacement, the best replacement was found to be 10% by weight of cement and the enhancement of compressive strength, split tensile strength and flexural strength were estimated to be 10.25%, 9.46%, and 12.34% respectively at 28 days curing. Among the concrete mixes prepared by incorporating both FA and MK, the best concrete mix was formed by incorporating 10% FA and 5% MK with 0.2% Recron 3s fiber (MK5FA10RF0.2). The enhancement in compressive strength, split tensile strength and flexural strength were estimated to be 6.92%, 4.50%, and 3.83% respectively over the conventional concrete at 28 days. Though the strength to cost ratio of replaced concrete is at par with conventional, the replacement reduces the consumption of cement. Similarly, the utilization of fly ash and MK makes the concrete sustainable and eco-friendly. A correlation among the compressive strength, split tensile strength and flexural strength have also been established.